Worksheets Electronic Development of STEAM-Based to Improve Students' Creative Thinking Ability - Deden Dicky Dermawan; Kinanti Andartiani (Hipotenusa : Journal of Mathematical Society, 2022)
This study aimed to develop a valid, practical, and effective STEAM-based E-LKPD to improve students' creative thinking skills. This study used research and development procedures with reference to the 4D model (Define, Design, Develop, and Disseminate) but this research is only up to the develop stage. The experimental design used is "One Groups Pretest-Posttest Design" with 72 students as research subjects. The research instruments include observation sheets, interview sheets, expert validation test sheets, written tests (pretest and posttest), and questionnaire sheets (questionnaire). The results of the research that have been gained, it is known that the validity of the E-LKPD according to the material expert validator is 91.6 in the very valid category, the media expert validator is 75 in the valid category, and the language expert validator is 85 in the very valid category. The effectiveness of E-LKPD according to the results of the N-Gain test calculation of 0.61 is included in the category of quite effective and showed that there was a significant increase in creative thinking skills before and after using STEAM-based E-LKPD with 91% classical completeness results with complete criteria. The STEAM-based E-LKPD was declared practical according to the results of teacher and student respondents who showed the results of teacher respondents, namely scores of 83 and 80 with very interesting categories and student respondents producing an average score of 81 with very attractive categories. The conclusion of the research is that the development of STEAM-based E-LKPD is suitable for distance learning activities and can improve students' creative thinking skills.